2022
DOI: 10.3390/healthcare10081372
|View full text |Cite
|
Sign up to set email alerts
|

Gallstone Is Associated with Metabolic Factors and Exercise in Korea

Abstract: Gallstone is a common health problem. Cholesterol stone accounts for 90% of stones in the United States and Europe, but East Asia has a high proportion of pigment stone. The aim of this study was to determine the relationship between modifiable metabolic factors and gallstone in a region with a high prevalence of pigment stone. Among 3159 participants who underwent health screening at Ulsan University Hospital from March 2014 to June 2019, 178 patients were diagnosed with gallstone using abdominal ultrasonogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 18 publications
2
1
0
Order By: Relevance
“…The Matsuda index value is a protective factor for GBS (OR = 0.59, 95% CI:0.39, 0.90, p < 0.05). This result is consistent with previous research results [23,24]. In a study that included 4125 Korean postmenopausal women [24], the results showed that in a multiple logistic regression analysis, LDL-C was an independent factor of GBS in premenopausal women and HOMA-IR was significantly associated with the occurrence of the GBS.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The Matsuda index value is a protective factor for GBS (OR = 0.59, 95% CI:0.39, 0.90, p < 0.05). This result is consistent with previous research results [23,24]. In a study that included 4125 Korean postmenopausal women [24], the results showed that in a multiple logistic regression analysis, LDL-C was an independent factor of GBS in premenopausal women and HOMA-IR was significantly associated with the occurrence of the GBS.…”
Section: Discussionsupporting
confidence: 92%
“…This result is consistent with previous research results [23,24]. In a study that included 4125 Korean postmenopausal women [24], the results showed that in a multiple logistic regression analysis, LDL-C was an independent factor of GBS in premenopausal women and HOMA-IR was significantly associated with the occurrence of the GBS. However, previous studies only analyzed the correlation between insulin levels and GBS, while we further adopted more accurate indicators that reflect islet β cell secretion levels and insulin resistance indexes, which can better verify that the severity of insulin resistance in T2DM patients is an independent risk factor for the incidence of GBS, and that the degree of islet β cell secretion is closely related to the incidence of GBS.…”
Section: Discussionsupporting
confidence: 92%
“…Males are affected by cholithiasis at early age which suggest that young men are probably have specific physiological process that increases the risk of stones formation. Including hormonal changes and metabolic process [44]. Changes in the laboratory parameters are probably related to the gender, living place, treatment choice including surgery or conservative, the used antibiotics, and the An association between the glucose level and the administration of pancreatin observed in male group.…”
Section: Discussionmentioning
confidence: 99%